Integration of Culture and Tourism: A Study Base on the Shaping, Communication and Effectiveness of Teng Wang Pavilion Branding - Li, Chenrui (International Journal of Social Sciences and Public Administration, 2024)
The Teng Wang Pavilion is one of the most esteemed tourist attractions in Nanchang City, Jiangxi Province. It is the sole 5A-level tourist attraction in the city, and its unique geographical location, profound historical heritage, and rich cultural inheritance have collectively attracted the attention of the majority of tourists. Furthermore, the Teng Wang Pavilion has made a significant and enduring contribution to the promotion of the local culture and tourism industry, as well as the development of the region's economic activities. At the same time, it has stimulated the development of innovative industries, such as the Teng Wang Pavilion itself as the theme of the cultural and creative industries. Moreover, it has also inspired the issuance and sale of cultural and creative products featuring the Teng Wang Pavilion, as well as the creation of a unique Nanchang cultural tourism logo, which has enhanced the brand awareness of the local cultural tourism industry. This paper takes Teng Wang Pavilion as an example and examines the history and current situation of the development of cultural and creative products in the context of the local cultural and tourism industry in Nanchang.